PERSONAL INCOME TAX GAPS: BIBLIOMETRIC AND ECONOMETRIC ANALYSIS - I. Tiutiunyk; O. Mazurenko (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The article is devoted to the essence and features of the formation of personal income tax gaps. The object of the paper is 1795 publications indexed in the Scopus database on the tax gaps in the national economy. The time horizon of the study was in 1935—2021.  On the basis of bibliometric analysis, the main directions of the study of tax gaps are determine, the trend of changing the number of publications on this issue is analyzed. It is concluded that the theory of tax gap management is quite young and is currently only in its infancy. By the VOSViewer tools, five patterns of frequency of use of keywords in scientific works devoted to the issues of forming tax gaps have been identified, their connection with other economic categories have been determined. The analysis of the publications indexed in the Scopus database on a geographical basis is carried out. Clustering international research networks based on bibliometric analysis of scientific papers on the theory of tax gaps management by geographical location have been done. The article identifies the top Scientific Journals indexed by the Scopus database in which the issues of tax gap management were published most often. According to the Scopus database the most popular theories within this problem are: social theories, inequality and tax morality, management and motivation theories, sustainable development theory, production theory, concepts of fiscal policy implementation. A methodical approach to the assessment of tax gaps for personal income tax is proposed. The personal income tax gaps for Ukraine and European Union countries has been estimated. An average volume of personal income tax gaps within 7—28 %, and there is no positive dynamics in its reducing. The countries with the highest volume of personal income tax gaps include Greece, Poland, the Slovak Republic, Turkey, with the lowest — Germany, Belgium, Latvia, Luxembourg. Based on the Multiple regressions test, the hypothesis about the significant impact of tax gaps on personal income tax on the country’s economic development indicators was tested. Graphical interpretation of the link between the personal income tax gap and GDP for Ukraine and European Union countries indicates a negative correlation between them.